Critical review of the internet crimes law in Turkey: Social structure, social media and legislative regulations - Akter, Tutku (Nova Science Publishers, Inc., 2016)
It is possible to say that social structures even if slowly change in time due to the various numbers of internal and external factors. The social structure, referring to all physical and cultural structures that deal with and covers the society in the most general manner, is a social asset, which includes social groups, entities and in where social relationships, events are comprised and population and settlement style are formed. These structures that may be defined as dynamic systems interact with other socio-cultural systems more easily through developing communication technologies particularly information technologies; therefore diffusion, transformation and change are inevitably occur accordingly. Thus, some ideological state apparatuses constitute “power” on society to bring the order and ensure ‘what the situation should be’. Legislature, executive and judiciary as well as media got recently involved can be considered as ideological apparatuses ensuring “what it should be”. The inspections, regulations and some enforcement on “what it should be” of relevant social systems are performed through control mechanisms under the state. As Bahar noted (2009), if case of arising of conflicts on benefit and power, laws step in as rules that officially build consensus. Therefore; the legal rules that are responsible from the inspection and order of social structures, must be dynamic just as social structures and change in parallel with social changes (Bruhl, 1991). It is no doubt that developed communication technologies bring many convenience and opportunities. However, the associated risks and threats should not be avoided. In that perspective of protecting the essence of existing structure, during the modernization process of any society, the ‘supervision’ and inspection of exposed transformations are performed through the laws and legal rules of that society. Hence this process also gives information about the situation of society on its “modernization” map. In this regard, the study will analyze the relevant law(s) on cyber crimes within the context of compliance of Republic of Turkey and its control mechanisms to social change processes, and current status in the modernization process will be assessed. Accordingly, the critical content analysis of “Law on Regulating Broadcasting in the Internet and Fighting Against Crimes Committed Through Internet Broadcasting” will be undertaken and solution recommendations will be seek. © 2016 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Legislative regulations; Modernization; Social media; Social structure